ANALISA PENGARUH KINERJA MANAJEMEN RANTAI PASOK TERHADAP PENILAIAN PELANGGAN RUMAH MAKAN AYAM BAKAR WONG SOLO CABANG MAKASSAR - Burhanuddin Baharuddin (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2015)
Analysis of Effect of Supply Chain Management Performance Against Customer Rating Restaurant Ayam Bakar Wong Solo Branch Makassar. This study aims to determine is there Effect of Supply Chain Management Performance Against Customer Rating Restaurant Ayam Bakar Wong Solo Branch Makassar. This study was carried out to customers who make a purchase at Ayam Bakar Wong Solo Branch Makassar where over three times the frequency of purchase. This study is a qualitative research method and an explanatory research design (explanatory research). Total sample of 100 customers. Data were analyzed using univariate and bivariate analysis. The results showed there was a significant relationship between the variables flexibility, quality of food and responsiveness in the supply chain performance grilled chicken restaurant Wong Solo Makassar branch at the high category.